Pengaruh Celebrity Endorsement dan E-Service Quality terhadap Customer Loyalty dengan Brand Image sebagai Variabel Intervening pada Konsumen Aerostreet di TikTok - Bil Ufuqil A’la; Mutamimah Mutamimah (ARZUSIN, 2025)
The rapid growth of digital commerce via social media platforms has driven shifts in marketing strategies, including the use of celebrity endorsement and the enhancement of electronic service quality, which directly affect brand image formation and customer loyalty. This study aims to analyze the influence of celebrity endorsement and e-service quality on customer loyalty, with brand image as an intervening variable among Aerostreet consumers on TikTok. A quantitative method with an explanatory research design was employed involving 100 respondents who had purchased Aerostreet products at least twice via TikTok Shop. Data were collected through an online questionnaire and analyzed using SmartPLS to test both direct and indirect relationships among the constructs. The results show that celebrity endorsement and e-service quality have a significant positive effect on brand image, and that brand image significantly affects customer loyalty. In addition, celebrity endorsement and e-service quality indirectly influence customer loyalty through brand image as a mediating variable. These findings underscore the importance of endorser credibility, electronic service quality, and brand image management in digital marketing strategies aimed at strengthening customer loyalty. The practical implications direct companies to optimize celebrity-based promotion and improve the quality of digital services in order to build long-term relationships with consumers in social media–based digital commerce ecosystems.